Thematic morning report in clinical training for critical care medicine resident physicians: Preliminary exploration in a tertiary hospital of China - Lei Zhang; Na Li; Yu Liu; Yan Li; Zhengwen Liu (PLoS ONE, 2025)
Morning report (MR) is one of the most important forms of resident standardized training. However, at present, it has not been carried out in most residential training bases in China. The specific content and implementation plan of MR lack standardized process. We introduced thematic MR in the training of residents who underwent standardized training in critical care medicine. A total of 37 residents (major in critical care medicine) were divided into two groups: the MR group (n = 22) and the traditional training group (n = 15). After receiving a 24-week training in the ICU of the Department of Critical Care Medicine, a comprehensive ability of critical care medicine was evaluated in the residents. The performance was assessed by Objective Structured Examination (OSCE) stations and theory examinations, including clinical decision-making ability, emergency treatment ability, clinical practice skills, communication and cooperation skills and medical theoretical knowledge. The results showed that, although there was no significant difference between the two groups in terms of communication and teamwork skills ( P = 0.524), the MR group outperformed the traditional training group in terms of clinical decision-making ability, emergency treatment ability, clinical practice skills, medical theoretical knowledge ( P < 0.05). Additionally, a questionnaire survey on the training mode of thematic MR in critical care medicine was conducted. The results showed that up to 90.9% (20/22) of residential physicians believed that thematic MR is necessary in the training of critical care medicine, and 86.4% (19/22) of them believed that the implementation of thematic MR could improve their mastery of knowledge in critical care medicine. In conclusion, this preliminary exploration demonstrated that thematic MR has the potential to enhance the training effect of residential physicians in critical care medicine. It is a favorite way among residents owing to its ease of implementation, flexibility, and hierarchical structure in the training of critical care medicine, offering a valuable complement to conventional training.